DUOLINGO GAMIFICATION: DOES IT REDUCE STUDENTS’ GRAMMATICAL ERRORS IN WRITING? - Mulyadi Syahputra (Getsempena English Education Journal, 2019)
The study is aimed to examine the effectiveness of Duolingo Gamification Platform to reduce the students' grammatical errors in writing a report text. The participant of this study were 25 students in the second grade of Methodist Senior High School in Banda Aceh, Indonesia. The research utilized a pre-experimental design with one group pre-test post-test. The instrument of this study is a test divided into pre and post-test. The data were analyzed using the t-test. The study revealed that the mean score of the pre-test is 53.8, and the mean score of post-test is 55.4. The standard deviation for pre-test was 7.18 and for post-test were 7.29 and the score of the standard of error of pre-test was 1.43 and post-test was 1.45. The t-score of the study was 4.0, with the degree of freedom 24,and the t-table was 1.69. The data showed that the t-score was higher than t-table, which leads us to the interpretation that the Ha was accepted and H0 was rejected. It indicated that the use of Duolingo Gamification platform was sufficient to reduce the students' grammatical errors in writing report text. Therefore, the platform was highly recommended to use to increase the quality of students’ writing skill, especially in the report text.